Local Fractional Hilbert-Type Inequalities with a Non-Homogeneous Kernel - Vuković, Predrag (Armenian Journal of Mathematics, 2025)
The main objective of this paper is to study some new local fractional Hilbert-type inequalities with a general kernel. We apply our main results to non-homogeneous kernels. In addition, we obtain the best possible constants.